The Influence of Brand Image, Electronic Communications fromWord of Mouth, and Product Quality on Acer Laptop PurchaseDecisions - Aswindra, Jordy Stephano; Purwadi, Purwadi (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
This study aims to determine the influence of brand image, electronic communication from word of mouth, and product quality to the purchase decision of Acer laptops. This type of research is a quantitative research with data sources obtained from primary data. This study used a sample of 95 respondents. Sampling was carried out using purposive sampling with the characteristics of the respondents, namely students of the Faculty of Economics and Business, Mulawarman University who are consumers of Acer laptops. In this study, the data collection technique was carried out using questionnaires distributed online. Data analysis using multiple linear regression with IBM SPSS tools statistics 29. Based on the analyzed data, it can be concluded that brand image, e-WOM, and product quality partially (individually) have a positive and significant effect on purchase decisions. then for simultaneous testing, it was found that the variables of brand image, e-WOM, and product quality together had a significant effect on the purchase decision